2015
DOI: 10.1038/srep09047
|View full text |Cite
|
Sign up to set email alerts
|

An adenosine A3 receptor agonist inhibits DSS-induced colitis in mice through modulation of the NF-κB signaling pathway

Abstract: The role of the adenosine A3 receptor (A3AR) in experimental colitis is controversial. The A3AR agonist N6-(3-iodobenzyl)adenosine-5'-N-methyluronamide (IB-MECA) has been shown to have a clinical benefit, although studies in A3AR-deficient mice suggest a pro-inflammatory role. However, there are no studies on the effect of 2-Cl-IB-MECA and the molecular mechanism of action of A3AR in murine colitis models in vivo. Is it the same as that observed in vitro? The interaction between 2-CL-IB-MECA and A3AR in a muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 37 publications
4
45
0
Order By: Relevance
“…23 Out of many proinflammatory cytokines, TNF-α is known to have a crucial role in the pathogenesis of colitis and the clinical inhibition of TNF-α (infliximab and adalimumab) has been shown to reduce disease pathology and morbidity in IBD patients. 21,25 Moreover, it has also been reported that the increase in the production of proinflammatory cytokines and the expression of NF-κB signaling in the mucus of IBD patients and in the mouse DSS-induced acute colitis model. 21,25 Moreover, it has also been reported that the increase in the production of proinflammatory cytokines and the expression of NF-κB signaling in the mucus of IBD patients and in the mouse DSS-induced acute colitis model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Out of many proinflammatory cytokines, TNF-α is known to have a crucial role in the pathogenesis of colitis and the clinical inhibition of TNF-α (infliximab and adalimumab) has been shown to reduce disease pathology and morbidity in IBD patients. 21,25 Moreover, it has also been reported that the increase in the production of proinflammatory cytokines and the expression of NF-κB signaling in the mucus of IBD patients and in the mouse DSS-induced acute colitis model. 21,25 Moreover, it has also been reported that the increase in the production of proinflammatory cytokines and the expression of NF-κB signaling in the mucus of IBD patients and in the mouse DSS-induced acute colitis model.…”
Section: Discussionmentioning
confidence: 99%
“…23,25 Myeloperoxidase is an enzyme most abundantly found in azurophilic granules of neutrophils and monocytes. 23,25 Myeloperoxidase is an enzyme most abundantly found in azurophilic granules of neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A2aAR regulates several biological processes including inflammation. Upregulation of A2aAR reportedly suppressed inflammation in rats with colitis [28]. Therefore, we evaluated the role of A2aAR in UC.…”
Section: Discussionmentioning
confidence: 99%
“…They modulate NF‐κB, phosphoinositide‐3‐kinase–protein kinase B‐Akt (PI3K‐PKB/Akt), Wnt and mitogen‐activated protein kinase pathways. Expression of A 3 AdR is upregulated in patients with arthritis, Crohn's disease and colon cancer . It was demonstrated that sustained activation of A 3 AdRs with 2‐CI‐IB‐MECA impaired oligodendrocyte viability through generation of ROS and mitochondrial membrane depolarization …”
Section: Adverse Effects and Toxicity Of Adenosine Receptor Ligandsmentioning
confidence: 99%